NF-kappaB activity induced by inflammatory cytokines under transplantation environment impairs pancreatic islet survival and intraportal transplantation outcome - Chen, Chunguang; Justus Liebig University Giessen (My University, 2010)
Intraportal islet transplantation suffers from low efficiency caused by substantial islet mass loss after transplantation. We hypothesized that this process is induced by an environment of inflammatory cytokines and lack of oxygen under dynamic control of the transcription factor NF-kappaB. Here we show that cytokine-induced NF-kappaB activation in islet cells was compromised by hypoxia in a time-dependent manner which resulted in a diversely modulated NF-kappaB target gene expression profile. Ex vivo islet cell death analysis showed that proinflammatory cytokines alone did not cause evident cell death in pancreatic islet within 24 hours, while the combination of cytokines with hypoxia resulted in a strong induction of cell death that could be blocked dose-dependently by a selective IKK- inhibitor. Gene expression analysis revealed that cytokine-induced NF-kappaB activity promoted anti-apoptotic genes under normoxia whereas it repressed these genes under hypoxia, indicating that the pro-apoptotic role of NF-kappaB activity under hypoxia had resulted from its repression of anti-apoptotic genes. Functional studies were carried out using an intraportal transplantation model where porcine islets were infused to the liver of diabetic NMRI nu/nu mice. Immunohistochemistry study showed that NF-kappaB activation in the transplanted islets was detectable shortly after transplantation, however, its extent and intensity decreased by time. Systemic NF-kappaB inhibition by IKKbeta inhibitor administration in transplanted animals significantly prolonged islet graft survival and improved islet transplantation outcome. Immunohistochemical studies showed that systemic NF-kappaB inhibition at current dosage had no obvious impact on islet embolism-induced liver tissue necrosis or neutrophilic granulocyte migration/infiltration in the transplanted islets, indicating that the primary target of NF-kappaB inhibition is the transplanted islet. Collectively, these findings indicate that while NF-kappaB has an anti-apoptotic role under normoxia, hypoxic transplantation environment compromises its activity and transforms it to a pro-apoptotic transcription factor in pancreatic islets. We conclude that cell signaling therapy by NF-kappaB inhibition represents a suitable strategy to improve islet transplantation efficiency.

Die intraportale Inseltransplantation ist beeinträchtigt durch geringe klinische Wirksamkeit, da es zu einem schnellen Verlust der transplantierten Zellen kommt. Als wesentlichen Mechanismus hierfür wurde der Transkriptionsfaktor NF-kappaB vermutet, der für die Steuerung des Zellzyklus und insbesondere für die Apoptose von Betazellen verantwortlich ist. Als erstes fanden wir eine zeitabhängige Einschränkung der zytokin-induzierten NF-kappaB-Aktivierung in Inselzellen durch Sauerstoffmangel. Im Ergebnis wird das durch NF-kappaB aktivierte Genmuster durch Hypoxie erheblich verändert. Die Kombination aus proinflammatorischen Zytokinen und Sauerstoffmangel verursachte vermehrten Zelltod in isolierten Langerhansschen Inseln. Das Absterben der Zellen konnte durch die Anwesenheit von IKK-beta Inhibitor konzentrationsabhängig gebremst werden. Zytokine in normaler Sauerstoffumgebung induzierten keinen Zelltod innerhalb einer Beobachtungszeit von 24 Stunden. Die zytokininduzierte Aktivierung von NF-kappaB führte zur vermehrten Expression der anti-apoptischen Gene BCL-xL, c-FLIP and Survivin. Im Sauerstoffmangel wurde dieser Vorgang blockiert und es dominierten apoptotische Gene. Deutliche Hinweise einer nahezu sofortigen NF-kappaB Aktivierung fanden sich immunhistochemisch in Schweineinseln, die diabetischen Nacktmäusen intraportal infundiert worden waren. Diese Aktivierung war nur kurz nach Transplantation festzustellen, aber ihre gezielte Inhibition durch den IKK- Antagonisten führte zu einer signifikanten Verbesserung des langfristigen Transplantationserfolges. Es konnten keine Effekte der IKK-b Hemmung auf andere Zellen (Leber, neutrophile Granulozyten) außer Inselzellen festgestellt werden. Zusammenfassend fand sich eine anti-apoptotische Funktion von NF-kappaB bei normalem Sauerstoffdruck, aber eine pro-apoptotische Wirkung im Sauerstoffmangel. Weitere Untersuchungen müssen zeigen, ob die gezielte und kurzfristige Hemmung von NF-kappaB eine neue klinisch anwendbare Therapieform zur Vermeidung von frühem Transplantatverlust wird.
Keywords: intraportale Inseltransplantation; NF-kappa B; kappaB Activity; Intraportal Transplantation Outcome; ddc:610